Bladder neck contracture after radical prostatectomy: what is the reality of care? - Pfalzgraf, Daniel Philipp; Siegel, Fabian; Kriegmair, Maximilian; Wagener, Nina (Journal of endourology, 2017)
The only peer-reviewed journal focused on the rapidly moving field of 3D printing and related technologies, providing comprehensive coverage of academic research and industrial and commercial developments that have applications in medicine, education, food, and architecture.